Prototype development of computer and peripheral support system for GITN / Norsuzilawaty Che Hassan - Che Hassan, Norsuzilawaty (2008)
The main objective of research is to develop a prototype system of computer and peripheral support (CAPS) system for Government Integrated Telecommunication Network (GITN) Company. This system is developed to improve the current situation such as to make reports of computer peripheral problems and give feedback of report of computer and peripheral which is done manually. It focuses on the process of notifying problem of computer and peripheral, give feedback through the status report and producing the daily report of users' statistic of report problem. The user can use the computer and peripheral support system online for submission of the reports problem. The data are collected through interview the administrator and observation in GITN Company. This system is developed using active server programming (ASP) language and MySQL as a database. This system provides a new method to improve the current process of the submission of status of report from manual system to online system.